An In Vitro Comparison of 5 Techniques for Impressing Dowel Space Preparations - Winston W. L. Chee, BDS,1 George C. Cho, DDS,2 and Riccardo Marzola, DDS3 (Blackwell Synergy, 2000)
This in vitro study compared 5 different dowel space impression techniques using polyvinyl siloxane impression material to determine which method produced fewer voids in the dowel space impression.